A linearization-based hybrid approach for 3D reconstruction of objects in a single image - Kotan, Muhammed; Öz, Cemil; Kahraman, Abdulgani (Zielona Góra: Uniwersytet Zielonogórski)
The shape-from-shading (SFS) technique uses the pattern of shading in images in order to obtain 3D view information. By virtue of their ease of implementation, linearization-based SFS algorithms are frequently used in the literature. In this study, Fourier coefficients of central differences obtained from gray-level images are employed, and two basic linearization-based algorithms are combined.
Keywords: 3D reconstruction; shape from shading; shape recovery; image comparison; surface inspection